The Influence Of Commitment, Service Quality and Bus Feasibility On Passenger Satisfaction In Corridor I Transjakarta Block M-City - Huda, Syahrul; Handayani, Susanty; Setyawati, Aswanti; Arifiani, Librita; Abidin, Zaenal (Yayasan Pendidikan Belajar Berdikari, 2024)
The research aims to measure the level of satisfaction among Transjakarta bus riders. The inadequate quality of Transjakarta bus services, particularly in terms of safety, comfort, convenience, easiness, and efficiency, has been the key reason why people choose private automobiles. Decreased dedication among Transjakarta bus crew contributes to bad customer experiences, while uncertainty in schedule adherence and journey duration, combined with Jakarta traffic congestion concerns, exacerbate the effectiveness of public transportation services. By solving these difficulties, it is believed that the Transjakarta bus service in Corridor I will improve passenger happiness, promote more efficient mobility, and reduce reliance on private vehicles, thereby helping to alleviate general traffic congestion. In this thesis, the author takes a qualitative approach and uses the Analytical Hierarchy Process (AHP) as an analytical tool. The goal of this study is to look at the outcomes of the four factors used to evaluate passenger satisfaction: commitment, service quality, and bus feasibility. As of now, no assessment results indicate that one criterion is superior to another. The consistency level of the four criteria, as well as their sub-criteria, was then assessed based on respondents' ratings. Finally, analyzing passenger satisfaction on Transjakarta buses using the established criteria and sub-criteria. The findings of the four criteria demonstrate a trend for 29% commitment, 28% service quality, and 19% bus feasibility, with stable consistency. The research findings and calculations show an Excellent rating based on the assessment criteria in the four major aspects of commitment, service quality, and bus feasibility.